ELECTRICAL CONDUCTION, dielectric BEHAVIOR AND MAGNETOELECTRIC EFFECT IN (1-x) Co1.2Mn0.2Fe1.6O4 + (x) BaTiO3 ME Composites - SAWANT, S. S.; GAIKWAD, P. K. (Innovare Journal of Sciences, 2020)
Objective: Electrical and magnetoelectric properties of magnetoelectric (ME) composites ferroelectric as electric component and a mixed ferrite as magnetic component are reported. The (1-x) Co1.2Mn0.2Fe1.6O4 + (x) BaTiO3 magnetoelectric (ME) composite have been prepared using conventional double sintering ceramic process where x varies as 0.00, 0.25, 0.50, 0.75 and 1.00. The X-ray diffraction pattern of the composites reveals the formation of spinel structure for the piezomagnatic phase and tetragonal perovskite structure for the piezoelectric phase without any other phase formation. The dc resistivity was measured as a function of temperature. The variation of dielectric constant ' dielectric loss ε'' and dielectric loss tangent δ with frequency in the range 1kHz-1MHz was studied. The dielectric constant shows dispersion in the lower frequency region, with almost a constant value at higher frequencies. The magnetoelectric voltage coefficient (dE/dH)H was studied as a function of intensity of the magnetic field. The measured magnetoelectric (ME) response demonstrated strong dependence on the volume fraction of CoMnFe2O4 and the applied magnetic field. A large ME voltage coefficient of about 647 Vcm-1Oe-1 was observed for 25% CoMnFe2O4 + 75% BaTiO3composite. Materials and Methods: The piezoelectric phase Barium Titanate (BaTiO3) was prepared by standard doubling sintering ceramic method using AR grade oxides/carbonate. Barium carbonate (BaCO3) and Titanium-dioxide (TiO2) were taken in molar proportion. Results: The electrical resistivity of ferrite phase is less as compared to the resistivity of ferroelectric material. The resistivity of composites is found to be in between ferrite and ferroelectric. Conclusion: Magneto-electric conversion factor with varying magnetic field shows maxima in the curve at a lower magnetic field and then decreases continuously at higher magnetic field. As ferroelectric content increases both the resistivity and magnetoelectric conversion factor also increases.